2019
DOI: 10.29252/jafm.12.06.29510
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Timing and Pattern of Fuel Injection on Performance and Emissions of a Diesel Engine in the Low-Temperature Combustion Mode – An Experimental Investigation

Abstract: This paper deals with experimental investigations on a four-cylinder, four-stroke, direct injection, turbocharged engine to evaluate effects of fuel injection strategies, exhaust gas recirculation (EGR) and intake boost pressure on the low temperature combustion (LTC) mainly to reduce nitric oxides (NOx) and smoke emissions keeping a concern on indicated mean effective pressure (IMEP). First, single-pulse fuel injection strategy with various fuel injection timings is tried to find the best operating conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Fang et al 9 examined the influence of pilot injection on emissions from a heavy-duty engine and found a dramatic decrease in NOx emission as the pilot injection quantity increased. Ramesh et al 10 investigated the effect of injection timing on NOx emissions from a diesel engine, which showed that the retarded main injection timing, along with pilot and post, significantly reduced NOx emissions without compromising power output and thermal efficiency. Fayad et al 11 attempted to study the effect of EGR on NOx emissions from diesel engines using different types of fuels and concluded that the use of different rates of EGR reduced the maximum peak cylinder pressure as compared to no EGR, and that the use of 30% EGR reduced NOx emissions for all fuels as compared to 15% EGR.…”
Section: Introductionmentioning
confidence: 99%
“…Fang et al 9 examined the influence of pilot injection on emissions from a heavy-duty engine and found a dramatic decrease in NOx emission as the pilot injection quantity increased. Ramesh et al 10 investigated the effect of injection timing on NOx emissions from a diesel engine, which showed that the retarded main injection timing, along with pilot and post, significantly reduced NOx emissions without compromising power output and thermal efficiency. Fayad et al 11 attempted to study the effect of EGR on NOx emissions from diesel engines using different types of fuels and concluded that the use of different rates of EGR reduced the maximum peak cylinder pressure as compared to no EGR, and that the use of 30% EGR reduced NOx emissions for all fuels as compared to 15% EGR.…”
Section: Introductionmentioning
confidence: 99%
“…Combustion strategies such as low-temperature combustion (LTC), homogeneous charge compression ignition (HCCI), and partially premixed combustion (PPC) are applied so that the engine could produce low soot and NOX emission (An et al 2018;Mathivanan et al 2019). However, these methods should be coped with some difficulties such as controlling combustion with a knock, high level of noise, weak cold start capability, and phase control (Calam et al 2019).…”
Section: Introductionmentioning
confidence: 99%